Estimation of personal ozone exposure using ambient concentrations and influencing factors. (August 2018) - Niu, Yue; Cai, Jing; Xia, Yongjie; Yu, Haofei; Chen, Renjie; Lin, Zhijing; Liu, Cong; Chen, Chen; Wang, Weidong; Peng, Li; Xia, Xiaoling; Fu, Qingyan; et al.
Abstract: Evidence is limited regarding whether ambient monitoring can properly represent personal ozone exposure. We conducted a longitudinal panel study to measure personal exposure to ozone using real-time personal ozone monitors. Corresponding ambient ozone concentrations and possible influencing factors (meteorological conditions and activity patterns) were also collected. We used linear mixed-effect models to analyze personal-ambient ozone concentration associations and possible influencing factors. Ambient ozone concentrations were around two to three times higher than personal ozone (43.1 μg/m 3 on average) and their correlations were weak with small slopes (0.35) and marginal R square (RM 2 ) values (0.24). Larger RM 2 values were found under high temperature (>29.5 °C), low humidity (<62.1%), good ventilation conditions (>4 h) and for individuals spent longer time outdoors (>0.6 h). In final model, personal ozone exposure was positively associated with ambient concentrations and ventilation conditions, but inversely correlated with ambient temperature and humidity. The models explained >50% of personal ozone concentration variabilities. Our results highlight that ambient ozone concentration alone is not a suitable surrogate for individual exposure assessment. Meteorological conditions (temperature and humidity) and activity patterns (windows opening and outdoor activities) that affecting personal ozone exposure should be taken into account. Highlights: We conducted repeated personal exposure measurements among adults in Shanghai. Ambient ozone concentration is 2 to 3 times higher than personal exposure level. Ambient ozone concentration alone is not a suitable proxy for personal exposure. Meteorological conditions and activity patterns affect personal ozone exposure. Our final model explains major variabilities of personal ozone concentrations.